2017
DOI: 10.14233/ajchem.2017.20702
|View full text |Cite
|
Sign up to set email alerts
|

Tribulus terrestris Extracts: An Eco-Friendly Corrosion Inhibitor for Mild Steel in H2SO4 Medium

Abstract: INTRODUCTIONThe use of mild steel in industries is due to its availability, good strength and comparatively low cost. The overall cost of metal is the total cost of itself plus its maintenance cost and it can be reduced by reducing the maintenance cost. The maintenance cost can be controlled and minimized. But presently in all countries, most of the industries are facing the problem of corrosion of mild steel in acidic medium [1]. It involves a significant cost expense for prevent or non-prevent of the metals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The fact that all linear correlation coefficients ( R ) are almost equal to one shows that plant extract adsorption on mild steel surfaces follows the Langmuir adsorption isotherm. The Langmuir isotherm implies inhibitor molecule monolayer adsorption, or the inhibitor molecule occupies one active site on a metal surface 58 . Furthermore, the Langmuir adsorption isotherm revealed that organic components in plant extracts with polar atoms or groups adsorbed on the metal surface may interact via mutual attraction or repulsion 59 .…”
Section: Resultsmentioning
confidence: 99%
“…The fact that all linear correlation coefficients ( R ) are almost equal to one shows that plant extract adsorption on mild steel surfaces follows the Langmuir adsorption isotherm. The Langmuir isotherm implies inhibitor molecule monolayer adsorption, or the inhibitor molecule occupies one active site on a metal surface 58 . Furthermore, the Langmuir adsorption isotherm revealed that organic components in plant extracts with polar atoms or groups adsorbed on the metal surface may interact via mutual attraction or repulsion 59 .…”
Section: Resultsmentioning
confidence: 99%